Crystal Structure and Magnetism of Potassium-Intercalated 2,7-Dimethylnaphthalene - Xiao-Lin Wu; Ren-Shu Wang; Hui Yang; Ming-An Fu; Hao Lv; Hua-Qing Yu; Xiao-Jia Chen; Yun Gao; Zhong-Bing Huang (Crystals, 2021)
The rich physical properties of metal-intercalated polycyclic aromatic hydrocarbon materials have recently attracted considerable attention. Crystals of potassium-intercalated 2,7-dimethylnaphthalene were synthesized via solid phase reaction. The combination of XRD measurements and first-principles calculations indicated that each unit cell contains two potassium atoms and four organic molecules. Magnetization measurements revealed that the samples show a Curie paramagnetism. Theoretical calculations showed that the intercalated structure becomes metallic and has local magnetic moment. Raman spectroscopy confirmed the migration of electron from potassium 4s to carbon 2p orbital, which is the source of magnetism. Our research on naphthalene derivatives is helpful for expanding the range of novel organic magnetic materials and organic superconducting materials.